KONSTRUKSI PEMIKIRAN SIBAWAIH DALAM KAJIAN IlMU NAHWU - Bustamin Dihe (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2018)
Sibawaih is one of the nahwu scholars of the Basra school, compiled the science of nahwu in his book known as al-Kitab, he was very careful in selecting the validity of one history, he also did not receive a linguistic argument which was not narrated in mutawatir and linguistic arguments in his book al-Kitab is a book of nahwu which he produces through a very obyektib study, because most of the methods used directly hear the language of the badwi and collect grammar perfectly in his time, and contribute a lot of thought to the reviewers of knowledge in the next generation to understand the language Qur'an as the holy book of Muslims